ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IV SD NEGERI 013857 MEKAR BARU PADA MATERI KPK - Anim, Anim; Hasibuan, Wilda Annisa; Rahmadani, Dila Oktapia; Putri, Arfika (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the mathematical communication skills of fourth-grade students of SD Negeri 013857 Mekar Baru on the Least Common Multiple (LCM) topic. This study uses a qualitative descriptive approach with 21 students as subjects. The research instrument is a written test compiled based on three indicators of mathematical communication skills, namely the ability to express mathematical ideas orally and in writing, the ability to use symbols, tables or pictures to convey mathematical ideas, and the ability to explain results and the process of solving with logical reasons. The results of the study show that in the first indicator, students' abilities are in the high category, although some students have not written complete explanations. In the second indicator, students' abilities are classified as low because there are still errors in solving using factor trees and prime factorization tables and the final results. While in the third indicator, students' abilities are in the medium category because some students have not provided appropriate reasons. Based on these results, it can be concluded that students' mathematical communication skills still need to be improved through learning activities that emphasize conceptual understanding and the ability to convey ideas clearly and structured.Keyword: mathematical communication; LCM; elementary students; descriptive qualitativeAbstrak: Penelitian ini bertujuan untuk menganalisis kemampuan komunikasi matematis siswa kelas IV SD Negeri 013857 Mekar Baru pada materi Kelipatan Persekutuan Terkecil (KPK). Penelitian ini menggunakan pendekatan desktiptif kualitatif dengan subjek sebanyak 21 siswa. Instrumen penelitian berupa tes tertulis yang disusun berdasarkan tiga indikator kemampuan komunikasi matematis, yaitu kemampuan mengungkapkan ide atau gagasan matematika secara lisan dan tulisan, kemampuan menggunakan simbol, tabel atau gambar untuk menyampaikan ide matematika, dan kemampuan menjelaskan hasil dan proses penyelesaian dengan alasan yang logis. Hasil penelitian menunjukkan bahwa pada indikator pertama kemampuan siswa berada pada kategori tinggi, meskipun beberapa siswa belum menuliskan penjelasan secara lengkap. Pada indikator kedua, kemampuan siswa tergolong rendah karena masih terdapat kesalahan dalam penyelesaian menggunakan pohon faktor dan tabel penyusunan faktorisasi prima serta hasil akhir. Sedangkan pada indikator ketiga, kemampuan siswa berada pada kategori sedang karena sebagian siswa belum memberikan alasan yang tepat. Berdasarkan hasil tersebut, dapat disimpulkan bahwa kemampuan komunikasi matematis siswa masih perlu ditingkatkan melalui kegiatan pembelajaran yang menekankan pemahaman konsep serta kemampuan menyampaikan ide secara jelas dan terstruktur.Kata kunci: kemampuan komunikasi matematis; KPK; siswa sekolah dasar; deskriptif kualitatif